Immortal by morning - Sands, Lynsay (Sands, Lynsay. Argeneau series, 2025)
Crispinus Delacort is an immortal rogue Enforcer and a homicide detective. But in his quiet city, he's more likely to be found rounding up truant teens than investigating murders. So when he learns that human bones have been found in the garden of a sprawling rural home, it's unexpected to say the least. Abril Newman can't believe her bad luck when she discovers a body buried on the grounds of her boss's home while chasing after Gina's mischievous lab, Lilith. She was just supposed to be house-sitting for a few days! And then Detective Delacort arrives. She knows she shouldn't be thinking about love when there's a crime scene outside the door. But ignoring her attraction to gorgeous Crispin is easier said than done. When Crispin realizes that a rogue is involved, he knows this won't be a simple investigation. Especially because he's so distracted by Abril's presence that all he wants is to kiss her senseless in every room of the manor. But he can woo her, solve the case, and stop a dangerous rogue by morning...right? --